Cadmium Exposure Alters Rhizospheric Microbial Community and Transcriptional Expression of Vetiver Grass - Wu, Bin; Li, Jia; Peng, Dinghua; Wang, Ziru; Xu, Heng (Frontiers in Plant Science, 2022)
Vetiver grass (Chrysopogon zizanioides L.) has been used to remediate cadmium (Cd)-contaminated soil, while there have been few studies on the influence of Cd exposure on the rhizospheric microbial community and transcriptional expression of C. zizanioides. In this study, we investigated the response of the rhizospheric microbial community and transcriptional expression of C. zizanioides in 20 mg/kg Cd-contaminated soil. The results showed that Cd levels in the roots and shoots of C. zizanioides reached 250.80 and 73.40 mg/kg, respectively. The Cd exposure changed the rhizospheric bacterial community, resulting in the significant enrichment of Sphingomonas, Lysobacter, and Gemmatimonadetes in Cd-contaminated soil. In addition, 880 and 3,419 differentially expressed genes were identified in the plant roots and shoots, respectively, in response to Cd stress. Among these, the overexpressed genes associated with redox homeostasis, glutathione (GSH) metabolism, cell wall biosynthesis, and transmembrane transport pathways were found to participate in Cd detoxification in C. zizanioides. These findings could be useful for understanding the selective variation of the rhizospheric microbial community and the detoxification mechanisms of C. zizanioides in Cd phytoremediation.